2000
DOI: 10.1523/jneurosci.20-24-08987.2000
|View full text |Cite
|
Sign up to set email alerts
|

D2Dopamine Receptors in Striatal Medium Spiny Neurons Reduce L-Type Ca2+Currents and Excitability via a Novel PLCβ1–IP3–Calcineurin-Signaling Cascade

Abstract: In spite of the recognition that striatal D(2) receptors are critical determinants in a variety of psychomotor disorders, the cellular mechanisms by which these receptors shape neuronal activity have remained a mystery. The studies presented here reveal that D(2) receptor stimulation in enkephalin-expressing medium spiny neurons suppresses transmembrane Ca(2+) currents through L-type Ca(2+) channels, resulting in diminished excitability. This modulation is mediated by G(beta)(gamma) activation of phospholipase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
380
6
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 461 publications
(414 citation statements)
references
References 57 publications
22
380
6
3
Order By: Relevance
“…The enhancement of paired pulse facilitation, together with the lack of any postsynaptic action of these compounds on IPSC reversal potential, holding current and membrane conductance, all point to a presynaptic site for this action. Accordingly, although DA receptors are abundantly expressed postsynaptically on striatal neurons (Surmeier et al 1996), their activation is known to modulate membrane conductances operating in voltage ranges far from the values chosen in this study to evoke synaptic events (Ϫ80 mV and Ϫ40 mV) (Schiffmann et al 1995;Surmeier et al 1995;Lin et al 1996;Hernandez-Lopez et al 2000). This observation, therefore, further confirms that the postsynaptic effects of DA receptor activation cannot be responsible for the observed modulation of striatal IPSCs.…”
Section: Discussionsupporting
confidence: 78%
“…The enhancement of paired pulse facilitation, together with the lack of any postsynaptic action of these compounds on IPSC reversal potential, holding current and membrane conductance, all point to a presynaptic site for this action. Accordingly, although DA receptors are abundantly expressed postsynaptically on striatal neurons (Surmeier et al 1996), their activation is known to modulate membrane conductances operating in voltage ranges far from the values chosen in this study to evoke synaptic events (Ϫ80 mV and Ϫ40 mV) (Schiffmann et al 1995;Surmeier et al 1995;Lin et al 1996;Hernandez-Lopez et al 2000). This observation, therefore, further confirms that the postsynaptic effects of DA receptor activation cannot be responsible for the observed modulation of striatal IPSCs.…”
Section: Discussionsupporting
confidence: 78%
“…DA can influence the activity of striatal spiny neurons by modulating voltage-dependent ion channels as well as excitatory and inhibitory synaptic inputs (Nicola et al, 2000). Although this generalization does not consistently apply, some studies have found that activation of D 1 -like receptors increases and D 2 -like receptors decreases membrane excitability of striatal neurons (Gonon, 1997;Hernandez-Lopez et al, 2000;West and Grace, 2002). The state of the neurons also influences the effects caused by DA.…”
Section: Dopamine Receptors In the Striatummentioning
confidence: 99%
“…Also, we cannot exclude that posttranslational modification (phosphorylation), which greatly affect NGFI-B activity (Maira et al, 2003), of pre-existing NGFI-B or de novo haloperidol-induced NGFI-B may play a role in the effects observed here. Other signaling pathways such as those implicating phospholipase C, intracellular calcium stores and protein kinase C (PKC) might also be involved (see Hernandez-Lopez et al, 2000). In addition, modulation of NGFI-B expression might also be indirect through modulation of glutamate neurotransmission by neuroleptic drugs (Leveque et al, 2000).…”
Section: Ngfi-b(+/+) Ngfi-b(-/-) Ngfi-b(+/+) Ngfi-b(-/mentioning
confidence: 99%